A Rare Case of an Intracardiac Myoepithelial Carcinoma in an Infant. Issue 4 (May 2019) - Patel, Priyal; Roberts, Ryan; Cole, Jason; Stalling, Melissa; Nicol, Kathleen; Hor, Kan; Bowman, Jessica; Setty, Bhuvana
Abstract : Myoepithelial carcinomas (MC) represent aggressive tumors that occur in a myriad of ages and anatomic locations. The rarity and histologic similarity with other tumors make them difficult to diagnosis. We report an extremely rare case of a right ventricular outflow tract mass identified to be an intracardiac MC in a 4-month-old male infant. Pathology revealed an EWS-KLF15 translocation. Treatment included gross total resection and intensive chemotherapy. Recurrent cardiac mass with brain metastasis was seen 16 months after primary diagnosis. We describe the rarity of intracardiac MC in pediatric patients and the challenges encountered in the multimodal management of this patient.